Green Job Opportunities Through the Curriculum and Community Enterprise for Restoration Science in New York City (Journal of Education and Development, 2021)
This paper examines the current understanding of the green economy movement and the critical role that education plays in attracting a viable workforce for this relatively new crusade. By connecting youth with the importance of environmental concerns in their community, tangible opportunities for sustainable change are created. By giving human agency to some of the most marginalized populations in New York City, the opportunity to experience environmental challenges in the community in which they live exposes these students to a plethora of enriching and rewarding employment opportunities. By combining the stewardship of their environment with formal and informal education, the Curriculum and Community Enterprise for Restoration Science in New York City is presenting multiple pathways for employment and educational opportunities in the green economy.